Cannery Row Movie Still - Chai Productions; Metro-Goldwyn-Mayer (MGM):::Creator::::::::::::
Doc (Nick Nolte) and Frank McRae (Hazel) trying to revive The Seer (Sunshine Parker), who has drowned. RESTRICTED USE